Evaluation the Role of Media and Language Policy in the Stabilization of Interethnic Relations at the Present Stage: The Example of a Multinational Kazakhstan - KASHKINBAYEV, А.Т.; GABDULINA, B.А.; KUZEMBAYEVA, А.О.; TAKIBAYEV, M.А.; ZHANPEYISOVA, К.D. (Journal of Advanced Research in Law and Economics, 2019)
Background: Theoretical and practical study of technologies for preventing and regulating inter-ethnic conflicts is an urgent problem for multinational Kazakhstan, which is undergoing the stage of statehood formation. The aim of the research is to analyze the place and role of democratic mass media and language policy in the system of mechanisms for improving national relations and to identify the main levers of influence on the formation of the language environment. Objectives: The object of the research is the analysis of the influence of mass media on the improvement of interethnic relations and aspects of the formation of the language environment as a factor in the development of interethnic relations. Method: The main research methods were expert evaluation, principles of unity and development, system and comparative analysis, socio-political and functional approaches, historical and comparative method, and content analysis. Results: The scientific result of the study was to identify the influence of mass media and language policy on the formation of civil society in a multinational Kazakhstan.It also reveals the dynamics of the language situation in the regions of the country in terms of its impact on inter-ethnic relations and determines the role of the language factor in the structure of ethnic identity of the largest ethnic groups in Kazakhstan. Conclusion: The results of this study can be used in the analysis of ethnopolitical situations in the regions of Kazakhstan, in the process of training journalists.